2016
DOI: 10.1084/jem.20161046
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cell effector commitment coupled to self-renewal by asymmetric cell divisions

Abstract: Nish et al. report that production of a fully committed Th1 effector cell occurs during an asymmetric cell division wherein the other daughter cell remains memory cell–like. Unequal transmission of metabolic signaling may be the driver of this regenerative behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 51 publications
4
101
2
Order By: Relevance
“…A later study showed that the CD8-high daughter cells retain higher mTORC1 activity (Figure 5), which drives c-Myc expression to promote glycolytic metabolism required for the effector CD8 T cell fate (Verbist et al, 2016). Bifurcation of PI3K/mTORC1 activity also contributes to differentiation fates in B cells and CD4 T cells (Lin et al, 2015; Nish et al, 2017; Pollizzi et al, 2016) (Figure 5). …”
Section: Pi3k In Innate and Adaptive Immunitymentioning
confidence: 99%
“…A later study showed that the CD8-high daughter cells retain higher mTORC1 activity (Figure 5), which drives c-Myc expression to promote glycolytic metabolism required for the effector CD8 T cell fate (Verbist et al, 2016). Bifurcation of PI3K/mTORC1 activity also contributes to differentiation fates in B cells and CD4 T cells (Lin et al, 2015; Nish et al, 2017; Pollizzi et al, 2016) (Figure 5). …”
Section: Pi3k In Innate and Adaptive Immunitymentioning
confidence: 99%
“…7, 2018; After acquisition, kidney biopsy samples were placed into HypoThermosol FRS preservation solution for 10-30 minutes on ice and then transferred to a cryovial containing 1 ml of CryoStor CS10 cryopreservation medium (BioLife Solutions). The cryovial was incubated on ice for [20][21][22][23][24][25][26][27][28][29][30] min and was then placed in a Mr. Frosty freezing container (Nalgene, #5100-0001) and transferred to a -80°C freezer overnight. Cryopreserved samples were then stored in liquid nitrogen and shipped on dry ice to the central processing site, where they were stored in liquid nitrogen until processing.…”
Section: Human Kidney Tissue and Urine Acquisitionmentioning
confidence: 99%
“…Recent evidence that unequal outcomes of proliferation or cell fate could be attributed to unequal nutritive signaling and mitochondrial dynamics in dividing stem cells, lymphocytes, and cancer cells [2-11] has converged with emerging evidence that metabolism plays deterministic roles in cellular fate and function in lymphocytes and many other cell types [2, 5, 7, 12-22]. This review will discuss recent advances in the regeneration of lymphocytes and how it has been seemingly patterned from an ancient duality of cellular feast and famine.…”
Section: Clonal Lymphocyte Regeneration Enabling Vertebrate Immunitymentioning
confidence: 99%
“…Emerging models point to a view that quiescent naïve and memory lymphocytes must engage in catabolic (or starvation) metabolism, including mitochondrial oxidative respiration, fatty acid oxidation, autophagy, and mitochondrial turnover and fission [2, 5, 7-9, 12, 42-51]. By contrast, the induction of proliferation and effector differentiation of lymphocytes is dependent on anabolic (or proliferative) metabolism, including PI3K/AKT/mTOR signaling, c-Myc induction, aerobic glycolysis (Warburg effect), glutaminolysis, inhibited autophagy, mitochondrial stasis, and mounting induction of reactive oxygen species.…”
Section: Binary Metabolism As a Framework For Cellular Switchingmentioning
confidence: 99%
See 1 more Smart Citation